Pengaruh Gymball dan Herbal Compress Terhadap Penurunan Kepala Dan Intensitas Nyeri Kala 1 Persalinan Fase Aktif - Setiana Andarwulan; Annah Hubaedah; Miftahul Hakiki (PROFESSIONAL HEALTH JOURNAL, 2022)
Childbirth in a woman begins when the uterus contracts with an increasingly frequent intensity. Labor that occurs in women who will give birth causes changes in the cervical area and affects the discharge of blood and mucus. Gymball is physical therapy or simple exercises using a ball. This exercise is applied to mothers who are pregnant, giving birth and postpartum. The ball used during labor in the active phase 1 has a big role in advancing labor, lowering the head or lowest fetal position, and reducing pain. The method used is a quantitative study, using a one group approach research design with a posttest only control design. In this design one group performs an assessment before and after being given treatment for a certain period of time. The population of mothers who gave birth was 40 respondents, with a sample of 34 respondents. With the sampling technique that is simple random sampling. Furthermore, prerequisite tests were carried out in the form of data normality tests and data linearity tests. If the prerequisite test is met, it can be continued with the T test. The results of the study obtained a pre-test normality test of 0.244 and a post-test of 0.200. The significance value is greater than 0.05 so that the data is normally distributed. The linearity test shows that the calculated value is greater than 0.05, namely p = 0.429. So that the prerequisite test is fulfilled. For the value of the T. test results of 0.000, p value <0.05, so there is an effect of gymball and herbal compresses on pain intensity. It is hoped that midwives and other health workers can apply non-pharmacological treatments, namely gymballs and herbal compresses to provide comfort to mothers who are giving birth.